Sensory processing in 16p11.2 deletion and 16p11.2 duplication. Issue 11 (2nd September 2022) - Smith, Harriet; Lane, Chloe; Al‐Jawahiri, Reem; Freeth, Megan
Abstract: Deletions and duplications at the chromosomal region of 16p11.2 have a broad range of phenotypic effects including increased likelihood of intellectual disability, autism, attention deficit hyperactivity disorder (ADHD), epilepsy, and language and motor delays. However, whether and how sensory processing is affected has not yet been considered in detail. Parents/caregivers of 38 children with a 16p11.2 deletion and 31 children with a 16p11.2 duplication completed the Sensory Behavior Questionnaire (SBQ) and the Child Sensory Profile 2 (CSP‐2) along with other standardized questionnaires assessing autistic traits (SRS‐2), ADHD traits (Conners 3), anxiety (SCAS‐P) and adaptive behavior (VABS‐3). SBQ and CSP‐2 responses found that sensory processing differences were clearly evident in both 16p11.2 deletion and 16p11.2 duplication, though there was significant variation in both cohorts. SBQ data indicated the frequency and impact of sensory behavior were more severe when compared to neurotypical children, with levels being similar to autistic children. CSP‐2 data indicated over 70% of children displayed clear differences in sensory registration (missing sensory input). Seventy‐one percent with 16p11.2 duplications were also unusually sensitive to sensory information and 57% with 16p11.2 duplications were unusually avoidant of sensory stimuli. This first detailed assessment of sensory processing, alongside other clinical features, in relatively large cohorts of children with a 16p11.2 deletion and 16p11.2 duplication demonstrates that sensory processing differences have a profound impact on their lives. Lay Summary: Responses to everyday sensory experiences in 38 16p11.2 deletion children and 31 16p11.2 duplication children were assessed. The frequency and impact of sensory behaviour differences was profound, though there was significant variation in both groups. Overall, sensory behaviour was found to be similar to autistic children. In both groups, over 70% failed to effectively register sensory information. 71% of 16p11.2 duplication children were very sensitive to sensory information and 57% of 16p11.2 duplication children were very avoidant of sensory stimuli.